Increasing Competitiveness of the Agrarian Sector of the Regional Russian Economy Russia - G. Gurnovich, Tatyana; V. Agarkova, Lyubov; N. Usenko, Lyudmila; A.Ostapenko, Elena; ., . (International Journal of Engineering and Technology, 2018)
The Russian agro-food market is currently characterized by the imperfection of economic relations between the spheres of production, processing and marketing and by insufficient level of infrastructure development, which negatively affects the efficiency of agricultural production and weakens the competitive advantages of producers. The problem of ensuring the competitiveness of Russian agrarians worsened due to the events of foreign economic nature: Russia entering the World Trade Organization, food embargo, a drop in oil prices on world markets. The way out is seen in the interaction between the subjects of the food market on the basis of marketing and the creation of strategic production associations as an important element of the infrastructure of the agro-industrial complex (AIC). The present paper considers the possibility of using the marketing tool for interaction in the agricultural sector of the Russian economy under the conditions of the opposite tendencies of globalization: integration and disintegration. The aim of the study is to develop recommendations for ensuring the competitiveness of agricultural producers by interaction marketing techniques and the creation of strategic alliances. Therefore, models for identifying threats and opportunities for agricultural organizations are developed; the algorithm for state regional AIC development programs is justified, the scheme of marketing interaction between the subjects of the strategic association is improved; the methodology for assessing the synergetic effect from the formation of a strategic association of commodity producers is adapted. The theoretical and practical significance of the results obtained for the Russian AIC is to expand the toolkit for increasing the competitiveness of farmers through methods of marketing interaction, popular in international practice. The proposed recommendations can be used in making managerial decisions on the formulation of program-targeted strategies for regional AIC development Russia.Â Â